Understanding consciousness - Velman, Max. (London : Routledge Taylor & Francis Group, 2009)
The book is divided into three parts; Part one surveys current theories of consciousness, evaluating their strengths and weaknesses. Part two reconstructs an understanding of consciousness from first principles, starting with its phenomenology, and leading to a closer examination of how conscious experience relates to the world described by physics and information processing in the brain. Finally, Part three deals with some of the fundamental issues such as what consciousness is and does, and how it fits into to the evolving universe. As the structure of the book moves from a basic overview of the field to a successively deeper analysis, it can be used both for those new to the subject and for more established researchers. Understanding Consciousness tells a story with a beginning, middle and end in a way that integrates the philosophy of consciousness with the science. Overall, the book provides a unique perspective on how to address the problems of consciousness and as such, will be of great interest to psychologists, philosophers, neuroscientists and other professionals concerned with mind/body relationships, and all who are interested in this subject.
Includes bibliographical references and index.
Keywords: Consciousness